CORRELATION BETWEEN PRENATAL YOGA AND DELIVERY PROCESS AMONG MOTHERS IN INDEPENDENT MIDWIFE CLINIC “HARTI MUSTAQIM SUMOWONO”, SEMARANG, INDONESIA - Dian Febri Sarwendah; Dian Nirmala Sari; Rosalina Rosalina (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Childbirth is the culmination of a human pregnancy with the emergence of a newborn infant from its mother’s uterus. Factors that may extend or influence the duration of labor are uterine contraction, pelvic bone, pelvimetry, and presentation. Focusing on muscle control, breathing techniques, relaxation, and peace of mind, yoga played a key role in preparing the delivery process. Aims: The purpose of this study is to determine the relationship of prenatal yoga with the delivery process among mothers at Independent Midwife Clinic “Harti Mustaqim Suwono”, Semarang, Indonesia. Methods: The research method was correlative analytical with cross sectional approach. A total of 43 mothers who follow prenatal yoga in Independent Midwife Clinic “Harti Mustaqim Suwono” was involved in this study. Respondents were asked to fill the registration book for their visiting at the prenatal yoga facility, and their delivery process. The collected data was then analyzed statically using the Chi-square test. Result: Among the 43 pregnant mothers who registered yoga class at Harti Mustaqim Suwono clinic, the majority (81.4%) attended the class regularly, and 38 mothers experienced normal delivery. Among the mothers who join the class routinely, only 2.9% mothers were giving birth by cesarean section. The data shown the possibility requiring C-sections for delivery increased when the pregnant mothers skipped the class. From 8 mothers who not regularly presented in the prenatal yoga class, only 50% of them experienced normal delivery. The Chi-square test shows that the correlation between prenatal yoga and delivery process among mothers in Independent Midwife Clinic “Harti Mustaqim Sumowono”, Semarang, Indonesia, was significant (p value = 0.003). Conclusion: The results highlight that attending yoga class routinely will affect significantly to the delivery process. Mothers who practiced prenatal yoga are more likely to experience normal labor. The study suggested the needs of yoga practice during the pregnancy and childbirth.